A C / C composite cathode plate, combined electrode, preparation method and application thereof
By using a combined electrode of C/C composite cathode plate and TiMn alloy anode plate, the problems of insufficient material performance and low process efficiency in the electrolytic MnO2 industry are solved, and the electrolytic MnO2 production with low trough voltage and low energy consumption is achieved, which improves the product Crystal form and purity.
Patent Information
- Application Number
- CN202310625009.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-05-30
AI Technical Summary
In the existing electrolytic MnO2 industry, the performance of the anode and cathode materials is insufficient, which makes it difficult to regulate the crystal form, purity and electrical properties of the electrolytic MnO2, and has low process efficiency and high energy consumption, resulting in problems such as impurities introduction and plate damage.
The combined electrode of C/C composite cathode plate and TiMn alloy anode plate is adopted to improve the mechanical properties and conductivity of the cathode plate through specific preparation methods and process flows, and enhance the anti-passivation ability and manganese permeability of the anode plate.
Low-cell voltage and low-energy consumption production of electrolytic MnO2 are achieved, impurities are introduced, and the crystal form and purity regulation capabilities of MnO2 are improved, the service life of the plate is extended, and production costs are reduced.
Smart Images

Figure CN116693312B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode, in particular to a C / C composite cathode plate and a combined electrode, and also to a preparation method and application thereof, belonging to electrode materials and electrolytic MnO 2 Industrial technology field. Background Art
[0002] With the slogan of "energy conservation, emission reduction, quality improvement and efficiency enhancement", battery materials such as alkaline manganese, lithium battery and sodium battery as new energy sources have attracted much attention. 2 The material properties and preparation process of MnO have put forward higher requirements. 2 The crystal form of MnO2 is complex, including 5 main crystals such as α, β, and γ, and more than 30 secondary crystals. The performance of materials with different crystal forms is also different, among which the electrical properties of the γ crystal form are the best. 2 There are many types of crystal forms, poor controllability, and low purity, which limits the performance of the final battery product.
[0003] At present, electrolytic MnO 2 The main anode materials used in industry are pure titanium anode or Mn-infiltrated titanium anode plate. Pure Ti anode plate has high mechanical strength, corrosion resistance, low specific gravity, and the electrolytic MnO 2 The product has high chemical purity and good discharge performance, but it is very easy to passivate when electrolyzed in acidic electrolyte at high temperature, which will lead to increased cell voltage, increased electrolysis energy consumption and decreased efficiency. It is necessary to remove the Ti plate from the cell and strip off the MnO 2 The existing Mn-infiltrated titanium anode plate reduces the cell voltage of the Ti plate to a certain extent and improves the anti-passivation ability of the anode plate. However, the current preparation process of the Mn-infiltrated titanium anode plate and the electrolysis of MnO 2 The research on the electrolytic characteristics and electrolytic process of the process is not perfect. During the vacuum high-temperature manganese infiltration process, the Mn volatilization loss is serious, and the mechanical properties of the anode plate are seriously damaged after high-temperature manganese infiltration, resulting in the stripping of electrolytic MnO. 2 In order to maintain the mechanical properties as much as possible, it is often necessary to undergo a short high-temperature manganese infiltration, resulting in a low actual manganese infiltration depth and a small amount of manganese infiltration. The low amount of manganese infiltration limits the electrical properties of the manganese infiltrated titanium anode and limits the electrolytic MnO 2 The electrolysis process control window such as acidity and current density in the process limits the electrolysis of MnO 2 The crystal form, purity control and electrical properties.
[0004] On the other hand, electrolytic MnO 2The cathodes used are mainly Cu cathodes and graphite cathodes. Cu cathodes have good conductivity, but there is often an oxide film on the Cu surface. 2 When the power is turned off and the stripping is required, the protection of the external electric field will disappear, and the Cu cathode will dissolve in the electrolyte in small amounts and enter the electrolytic MnO 2 The product affects the final electrolytic MnO 2 The quality of Cu is also affected. Cu is prone to produce dendrites in the battery, which can cause the battery to short-circuit, greatly affecting the final battery performance. When used as a cathode, graphite electrodes have poor mechanical properties and a short life. During the electrolysis process, ions in the solution enter the lamellar structure, causing the lamellar structure to expand and fall off.
[0005] In order to achieve electrolytic MnO 2 For the purpose of industrial energy conservation and quality improvement, many enterprises and research institutions have done a lot of research in mineral source processing, plate preparation, production methods, etc. The patent with publication number CN101694001A discloses a method for preparing a TiMn coated anode plate with a surface Mn content of 20-35% and good metallurgical bonding obtained by high-temperature diffusion at 900-1300°C. However, the Mn content on the surface of the anode plate prepared by this method is limited, resulting in limited performance of the final anode plate. Moreover, the high reaction diffusion temperature of this method not only leads to high energy consumption but also great damage to the mechanical properties of the material itself. The patent "A method for preparing a high deformation resistance titanium anode for electrolytic manganese dioxide production" (publication number CN105887133A) discloses a method for preparing a high deformation resistance titanium anode for electrolytic manganese dioxide production, which obtains a titanium plate with high strength, deformation resistance and certain ductility by heat treating the titanium plate under a vacuum environment and then sandblasting or shot peening. However, the problem of high slot pressure and easy passivation of pure titanium plates has not been solved. In general, the performance of anode and cathode materials still restricts the electrolysis of MnO 2 Comprehensive performance and electrolytic MnO 2 Industrial production efficiency, energy consumption and output. Therefore, it is necessary to develop and combine electrolytic MnO with excellent comprehensive performance. 2 The anode materials and cathode materials used have great significance and research value. Summary of the invention
[0006] In view of the shortcomings of the prior art, the first object of the present invention is to provide a C / C composite cathode plate. The cathode plate has the advantages of low resistance, high strength, low density, good electrical properties, long-term stable use, etc., and is not easy to introduce impurities during use.
[0007] The second object of the present invention is to provide a method for preparing a C / C composite cathode plate. The method is simple, low-cost and suitable for industrial production.
[0008] The third object of the present invention is to provide a combined electrode which has good electrochemical performance, strong stability, high strength, is not easily damaged during use, has a long service life, and can adapt to high acidity and high current density environments.
[0009] The fourth object of the present invention is to provide an application of a combined electrode. The combined electrode is used to prepare electrolytic MnO 2 When the electrolytic MnO 2 The cell voltage is small, energy consumption is reduced, and impurities are not introduced. MnO can be electrolyzed under high acidity and high current density. 2 , which can effectively regulate the MnO 2 Crystal form and purity.
[0010] In order to achieve the above technical objectives, the present invention provides a method for preparing a C / C composite cathode plate, which comprises mixing raw materials including graphite powder, phenolic resin and carbon fiber, and then adding carbon nanotube slurry to obtain a mixture; evaporating the solvent from the mixture, and then adding the mixture into a mold for hot pressing to obtain a green body; and placing the green body in a carbonization furnace for carbonization treatment to obtain the green body.
[0011] As a preferred solution, the mass ratio of the graphite powder, phenolic resin, carbon fiber and carbon nanotubes is 55-65:20-30:8-12:2-4. Graphite powder and phenolic resin are used as the matrix. Graphite powder is the guarantee of the conductivity of the electrode plate, and the molecular chain segments of the phenolic resin undergo cross-linking reaction during the curing process to form a network structure to improve the binding force between the binder and the material. The appropriate proportion of graphite powder and phenolic resin can not only ensure the binding force but also effectively prevent the damage to the mechanical properties of the electrode due to defects formed by excessive shrinkage of the material after pyrolysis of the phenolic resin; carbon fiber is used as a reinforcing phase. When the content is too little, the reinforcing effect is not prominent enough. When the content is too much, the carbon fiber is not easy to disperse, which will also lead to a relative decrease in the mechanical properties of the electrode; carbon nanotubes can form a continuous conductive network, increase the conductivity of the electrode, and improve the wettability between the electrode and the electrolyte. When the amount is too little, the effect is not obvious enough, and when too much is added, the cost is high.
[0012] As a preferred solution, the carbon fibers include short chopped fibers and long carbon fibers. The length of the short chopped fibers is 3 to 5 mm. The length of the long carbon fibers is 8 to 12 mm.
[0013] As a preferred solution, the mass ratio of the chopped fibers to the long carbon fibers is 6 to 8: 2 to 4. When there are too many short fibers or long fibers, the fiber type is single, which will reduce the fiber reinforcement effect. At the same time, too many long fibers are not easy to disperse.
[0014] As a preferred solution, the carbon fiber is surface pretreated with a solution that can reduce the surface hydrophobicity and inter-fiber friction of the carbon fiber. The solution that can reduce the surface hydrophobicity and inter-fiber friction of the carbon fiber includes acetone, ethanol, nitric acid solution, and an aqueous solution containing a surfactant.
[0015] As a preferred solution, the carbon fiber surface pretreatment process is: immersing the carbon fiber in an acetone solution, stirring and dispersing, and then washing and drying.
[0016] As a preferred solution, the graphite powder is flake graphite powder with a particle size of 6 to 20 μm.
[0017] As a preferred solution, the phenolic resin is a thermosetting phenolic resin, and the thermosetting phenolic resin is a 2123 type phenolic resin.
[0018] As a preferred solution, the carbon nanotube slurry includes carbon nanotubes, polyvinyl pyrrolidone, N-methyl pyrrolidone and water. Carbon nanotubes are light, high-strength and have good electrical conductivity, and can enhance the mechanical properties of C / C composite materials and reduce electrical resistance.
[0019] As a preferred solution, the mass concentration of carbon nanotubes in the carbon nanotube slurry is 0.3-8%.
[0020] As a preferred solution, the carbon nanotubes are multi-walled carbon nanotubes.
[0021] As a preferred solution, the carbon nanotubes have a diameter of 40 to 60 nm and a length of 2 to 10 μm.
[0022] As a preferred solution, the preparation process of the carbon nanotube slurry is: grinding and dispersing the carbon nanotubes, polyvinyl pyrrolidone, N-methyl pyrrolidone and water in a sand mill, and then diluting the obtained slurry with water.
[0023] As a preferred solution, the carbon nanotube slurry is sprayed in a mixture including graphite powder, phenolic resin and carbon fiber in a spray form.
[0024] As a preferred solution, before the mixed material is subjected to hot pressing molding, it is subjected to secondary mixing by at least one of a V-shaped mixer, a three-dimensional mixer, a four-dimensional mixer, and a double cone mixer.
[0025] As a preferred solution, the hot pressing process is as follows: controlling the pressing pressure to 10-40 MPa, first heating to 100-120°C at a heating rate of 1-5°C / min and keeping warm for 0.5-1h, then continuing to heat to 160-190°C and keeping warm for 20-40min, then cooling and reducing pressure to a temperature of 90-110°C and a pressure of 3-8Mpa, and then continuing to cool to room temperature; the pressure reduction rate is a pressure reduction of 2-4MPa for every 10-20°C temperature reduction.
[0026] In the hot pressing process, the water vapor that may exist in the raw material can be removed in the temperature range of 100-120°C, and the material can be solidified in the range of 160-190°C. The step-by-step temperature and pressure reduction is conducive to reducing the defects of the green body caused by thermal stress. In addition, the cooling process can be cooled with the furnace, and the slow pressure relief can prevent the C / C composite cathode plate from being thermally deformed and causing defects during the cooling process.
[0027] As a preferred solution, the carbonization process is as follows: in a protective atmosphere, the temperature is raised to 160-190°C for 0.5-1h and kept for 10-30min, the temperature is raised to 240-300°C for 2-3h and kept for 10-30min, the temperature is raised to 390-450°C for 4-6h and kept for 10-30min, the temperature is raised to 580-620°C for 25-30h and kept for 4-6h, the temperature is raised to 840-860°C for 6-8h and kept for 5-8h, then the temperature is lowered to 580-620°C for 4-6h and kept for 1-2h, and the temperature is lowered to 390-430°C for 1-2h and then naturally cooled to room temperature. In the carbonization process, the slower heating rate is to allow the phenolic resin to be stably decomposed and reduce defects in the blank caused by too fast decomposition.
[0028] As a preferred solution, the protective atmosphere is nitrogen or argon. Nitrogen with a purity greater than 99.99% is more preferred. The carrier gas rate of the protective atmosphere is 1 to 10 L / min. Continuous carrier gas is carried out during the carbonization process, and smooth ventilation and exhaust are conducive to the timely discharge of decomposition products. Among them, the carrier gas rate is mainly determined by the amount of green billets during carbonization. When the amount of green billets is large, the amount of phenolic resin decomposed per unit time is large, and a large carrier gas rate is required to discharge the decomposition products in time.
[0029] The present invention also provides a C / C composite cathode plate, which is prepared by the above method. The cathode plate has low resistance, high strength and low density, about 1.3-1.9 g / m 3 , good electrical performance, strong stability and long service life.
[0030] The present invention also provides a novel combined electrode, which includes the above-mentioned C / C composite cathode plate and TiMn alloy anode plate. The combined electrode has good electrochemical performance, strong stability, high strength, is not easy to be damaged during use, has a long service life, and can adapt to high acidity and high current density environments.
[0031] As a preferred solution, the preparation process of the TiMn alloy anode plate is as follows: coating a manganese-containing slurry on the surface of a titanium substrate to obtain a TiMn green body; performing low-temperature degreasing and dehydrogenation on the TiMn green body under vacuum conditions not exceeding 600°C, then filling it with an inert gas and heating it to a temperature not exceeding 800°C for medium-temperature manganese infiltration, and then continuing to heat it to above 850°C for high-temperature manganese infiltration to obtain a TiMn-Ti plate; and immersing the TiMn-Ti plate in an acid solution and then washing it to obtain a TiMn alloy anode plate.
[0032] In the process, the gas pressure value is designed according to the vapor pressure data of Mn at different temperatures to prevent manganese volatilization, reduce raw material loss and equipment damage, and at the same time make manganese have a higher manganese potential when diffusing into Ti at high temperature, reduce sintering temperature, reduce energy consumption, and increase manganese content in Ti plate. In addition, two-step diffusion can be achieved by segmented manganese infiltration, thereby improving the diffusion and penetration efficiency of manganese. Specifically, the process includes: (1) placing the TiMn green body under high vacuum conditions for low-temperature dehydrogenation and degreasing to remove the added dispersant, and dehydrogenating the surface of the hydrogenated titanium plate to expose the active titanium surface to ensure the subsequent manganese infiltration; then filling in inert gas to increase the gas pressure in the furnace, which can make heat transfer better, temperature uniform, and shorten the insulation time. On the one hand, it can ensure the activity of Ti plate and Mn powder, and on the other hand, it can ensure that Mn does not volatilize, increase Mn potential, and strengthen diffusion. Under this pressure condition, medium-temperature manganese infiltration is first performed, which can form a sintering neck between the Ti matrix and the Mn powder and between the Mn particles, forming a diffusion channel, and performing pre-diffusion. This step can ensure that less shrinkage occurs when sintering necks are formed between the Ti plate and the Mn powder particles and between the Mn powder particles, and prevent relative movement between the Ti plate and the Mn powder due to the difference in shrinkage (the Mn powder layer shrinks greatly during sintering, while the Ti plate does not shrink), which hinders the formation of a sintering neck between the Ti plate and the Mn powder particles, and is not conducive to the diffusion of Mn into Ti. At the same time, it also prevents the Mn layer from being densified too quickly at high temperature, thereby reducing the surface diffusion channels for rapid atomic diffusion, providing a large number of surface diffusion channels for high-speed atomic diffusion for subsequent high-temperature diffusion, and promoting manganese infiltration; (2) high-temperature manganese infiltration is carried out, and the high-temperature conditions can further promote the rapid diffusion of Mn, form a diffusion layer, and increase the amount of manganese infiltration.
[0033] As a preferred solution, the titanium substrate is pretreated by sandblasting and oxalic acid surface hydrogenation.
[0034] Sandblasting the surface of the titanium substrate can increase the surface energy of the Ti plate, refine the grains on the surface of the Ti plate, and increase the grain boundaries, so that during the high-temperature manganese infiltration process of the TiMn green material, more Mn atoms can diffuse rapidly into the Ti plate along the grain boundaries on the surface of the Ti plate in the form of grain boundary diffusion. At the same time, sandblasting can also remove the oxide layer and pollutants on the surface of the Ti plate, increase the surface roughness, and facilitate the attachment of the slurry during the subsequent Mn coating; oxalic acid hydrogenation treatment of the titanium plate surface can form hydrides on the Ti surface, so that the Ti plate can obtain a highly active Ti plate surface through dehydrogenation during the heating process, which is beneficial to the reaction and diffusion of Mn and Ti in the subsequent high-temperature manganese infiltration process and promotes manganese infiltration.
[0035] As a preferred solution, the titanium substrate is a TA1 type titanium plate or a TA2 type titanium plate. The thickness of the titanium substrate is 1.5 to 2 mm.
[0036] As a preferred solution, the mass concentration of the oxalic acid is 5% to 15%. Oxalic acid is an organic weak acid with good safety, and its reaction with Ti is easy to control.
[0037] As a preferred solution, the oxalic acid surface hydrogenation treatment process is: boil the oxalic acid solution for 3 to 5 minutes, and then put the titanium plate into the boiling and soaking for 40 to 60 minutes.
[0038] As a preferred solution, the pretreatment process is: cutting and dividing the titanium substrate, sandblasting, washing, oxalic acid surface hydrogenation treatment, washing and drying in sequence.
[0039] As a preferred solution, the manganese-containing slurry includes manganese powder and an organic dispersant.
[0040] As a preferred solution, the particle size of the manganese powder is 10 to 80 μm.
[0041] As a preferred solution, the organic dispersant is a water-soluble organic dispersant or a non-water-soluble organic dispersant. A non-water-soluble organic dispersant is more preferred. Water-soluble organic dispersants include gum arabic solution, polyvinyl alcohol solution, etc. Non-water-soluble organic dispersants include polyvinyl butyral organic solution, etc.
[0042] As a preferred solution, the organic dispersant is polyvinyl butyral ethanol solution. Using a non-water-soluble organic dispersant (such as polyvinyl butyral ethanol solution) can prevent the Mn powder from being oxidized during the preparation process.
[0043] As a preferred solution, the organic dispersant is a mixture of ethanol and polyvinyl butyral.
[0044] As a preferred solution, the mass ratio of ethanol to polyvinyl butyral is 8:1-4.
[0045] As a preferred solution, the mass ratio of the manganese powder to the organic dispersant is 0.2 to 2:1.
[0046] As a preferred solution, the preparation process of the manganese-containing slurry is as follows: after the manganese powder and the organic dispersant are stirred and mixed, vacuum degassing is performed to obtain a suspension slurry. The stirring and mixing is preferably ultrasonic stirring and mixing. The use of ultrasonic stirring can make the Mn powder fully dispersed and uniform. The vacuum degassing is mainly to remove oxygen in the slurry to prevent the Mn powder from being oxidized during the slurry preparation and Mn coating process, and also to prevent the formation of bubbles in the Mn coating layer during the Mn coating process and subsequent vacuuming to destroy the integrity and uniformity of the Mn coating layer.
[0047] As a preferred solution, the coating method is scraping or spraying.
[0048] As a preferred solution, the coating thickness is 100-300 μm. Controlling the coating thickness within a suitable range is conducive to obtaining a TiMn alloy material with excellent performance. Too small a coating thickness may result in insufficient Mn source, while too large a coating thickness may result in a waste of Mn powder.
[0049] As a preferred solution, after coating the manganese-containing slurry, static drying and vacuum drying are performed, wherein the static drying time is 30 to 60 minutes, and the vacuum drying temperature is 60 to 80° C. and the time is 1 to 2 hours.
[0050] As a preferred solution, the low-temperature degreasing and dehydrogenation process is: -4 ~10 -2 Under the vacuum pressure of Pa, the temperature is kept at 100-120℃ for 0.5-1h, then at 350-550℃ for 2-4h, and then at 550-600℃ for 1-2h. During the low-temperature treatment process, the temperature condition of 100-120℃ is the dehydration stage, which mainly removes the moisture and gas adsorbed during the transfer process; the temperature condition of 350-550℃ is the degreasing stage, and the organic dispersant (such as PVB) begins to decompose at about 350℃, and the decomposition is basically completed at 550℃; the temperature condition of 350-600℃ is the dehydrogenation stage, which can decompose the thin titanium hydride layer on the surface of the Ti plate to form a highly active titanium surface.
[0051] As a preferred solution, the inert gas is charged to a pressure of 1Pa to 25kPa. The inert gas is argon. After the dehydrogenation is completed, in order to increase the manganese diffusion amount, a certain amount of inert gas is charged to a pressure of 1Pa to 25kPa according to the saturated vapor pressure data of manganese at medium and high temperature manganese diffusion temperature. Since nitrogen will react with Ti at high temperature to form titanium nitride, inert gas is selected to adjust the gas pressure.
[0052] As a preferred solution, the medium-temperature manganese diffusion process is: keep the temperature at 750-800°C for 1-2 hours. Under this temperature condition, medium-temperature diffusion can be performed to form a sintering neck and a diffusion channel. Since the temperature is not high and the connection between the materials is mainly point contact, the atoms are mainly diffused on the surface, which can reduce the sintering shrinkage of the Mn layer when the sintering neck is formed, reduce the displacement between it and the non-shrinking Ti plate, and better form a diffusion channel.
[0053] As a preferred solution, the high temperature manganese infiltration process is: keeping the temperature at 850-950°C for 2-4 hours. Under this temperature condition, the diffusion speed is faster, the manganese infiltration can be rapid, and the densification of the manganese coating layer can be promoted. At the same time, this temperature has little effect on the mechanical properties of the Ti substrate, and the original ductility of the Ti plate can be maintained.
[0054] As a preferred solution, the acid solution is dilute sulfuric acid. The acid solution can be used to remove excess unreacted pure Mn powder on the sample surface. In addition, the use of dilute sulfuric acid can ensure that the manganese diffusion layer is not damaged.
[0055] As a preferred solution, the concentration of the dilute sulfuric acid is 0.2-1.5 mol / L.
[0056] The present invention also provides an application of a novel combined electrode, which is used in preparing electrolytic MnO 2 The combined electrode was used to prepare electrolytic MnO 2 When the electrolytic MnO 2 The cell voltage is small, energy consumption is reduced, and impurities are not introduced. MnO can be electrolyzed under high acidity and high current density. 2 , which can effectively regulate the MnO 2 Crystal form and purity.
[0057] As a preferred solution, the preparation of electrolytic MnO 2 During the process, the electrolysis temperature is 96-98°C and the electrolyte system is MnSO 4 -H 2 SO 4 , where Mn 2+ The concentration is 0.4~0.7mol / L, H 2 SO 4 The concentration is 0.3~0.8mol / L, and the current density is 40~110A / m 2 .
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] (1) By adding carbon nanotubes to the C / C composite cathode plate, the mechanical properties of the cathode plate are significantly improved and its resistance is reduced. At the same time, through a specific preparation method, the cathode plate has the advantages of low resistance, high strength, low density, good electrical properties, and long-term stable use, and it is not easy to introduce impurities during use;
[0060] (2) The TiMn alloy anode plate has a high manganese content, strong resistance to passivation, good acid corrosion resistance, good strength and ductility, excellent electrical and mechanical properties, and can adapt to high acidity and high current density environments;
[0061] (3) The combined electrode of C / C composite cathode plate and TiMn alloy anode plate has the advantages of good electrochemical performance, strong stability, high strength, etc. It is not easy to be damaged during use and has a long service life. It can also extend the plate out of the slot cycle, improve production efficiency, and reduce the replacement cost of the plate;
[0062] (4) Combined electrode for preparing electrolytic MnO 2 The electrolytic MnO 2 The cell voltage is small, energy consumption is reduced, impurities are not introduced, and MnO can be electrolyzed under high acidity and high current density. 2 , broaden the electrolytic MnO 2 The control range of acidity and current density in the process can effectively control the MnO 2 Crystal form and purity, so as to obtain electrolytic MnO with higher purity and better crystal form 2 ;
[0063] (5) The preparation method is simple, low-cost, green and environmentally friendly, and suitable for industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a microscopic metallographic photograph of the C / C composite material cathode plate prepared in Example 1.
[0065] Figure 2 This is a microscopic morphology of the surface of the TiMn alloy anode plate prepared in Example 1.
[0066] Figure 3 This is a microscopic morphology of the cross section of the TiMn alloy anode plate prepared in Example 1.
[0067] Figure 4 This is the XRD pattern of the surface of the TiMn alloy anode plate prepared in Example 1.
[0068] Figure 5 These are macroscopic photographs of the C / C composite cathode plate and the TiMn alloy anode plate prepared in Example 1, wherein (a) is the C / C composite cathode plate; and (b) is the TiMn alloy anode plate.
[0069] Figure 6 MnO prepared under the conditions of Example 1 2 XRD pattern of . DETAILED DESCRIPTION
[0070] The present invention will be further described below in combination with specific examples based on the technical solution of the present invention, but the protection scope of the present invention is not limited to the following embodiments.
[0071] Example 1
[0072] (1) Preparation of TiMn alloy anode plate
[0073] First, select a 1.5mm thick industrial TA1 titanium plate and cut the Ti plate into 40mm×80mm size. Sandblast the surface of the Ti plate until the surface is rough. After washing with water, ethanol, and water, immerse the treated Ti plate in a boiling 10% oxalic acid solution for 60 minutes for surface hydrogenation treatment, water washing, and vacuum drying. Then, mix ethanol and PVB powder in a mass ratio of 8:3, stir well to prepare an organic dispersant, and set aside. Select 30μm electrolytic Mn powder, mix the electrolytic Mn powder and organic dispersant in a mass ratio of 1:1, and form a stable suspension slurry through ultrasonic stirring and vacuum degassing. After that, a 150 μm thick Mn layer is evenly coated with a coater, left to dry for 30 minutes, and then transferred to a vacuum oven to dry at 80°C for 1 hour. After cooling, the green blank is taken out and transferred to a sintering furnace, and kept at 120°C for 0.5h in a vacuum environment; 350°C for 1h, 450°C for 1h, 550°C for 1h; and then 600°C for 0.7h. After the insulation is completed, argon is filled until the pressure in the furnace is 100Pa, and then the temperature is raised to 800°C for 1h, 900°C for 2h, and after the insulation is completed, it is cooled and taken out of the furnace. Finally, the prepared TiMn-Ti plate is soaked and cleaned with 0.5mol / L dilute sulfuric acid until no bubbles are generated, then it can be taken out, cleaned and dried to obtain a TiMn alloy anode plate.
[0074] After testing, the tensile strength of the TiMn alloy anode plate is 420mPa, the elongation is 23.3%, the surface Mn content is 64.2%, and the main phase on the surface of the plate is TiMn. 2 ( Figure 4 ).from Figure 1 It can be seen that the surface of the TiMn alloy anode plate is relatively rough, which is conducive to the 2 The nucleation and adhesion of the nanostructured carbon nanotubes are enhanced, and the rough surface can increase the specific surface area and effectively reduce the tank pressure. Figure 2 It can be seen that the manganese-diffused layer is divided into four layers: the surface manganese-rich layer, the middle transition layer, the middle needle-shaped layer, and the inner layer of pure Ti.
[0075] (2) Preparation of C / C composite cathode plate
[0076] First, the short carbon fiber with a length of about 4 mm and the long carbon fiber with a length of about 9 mm are soaked in acetone to treat the surface, stirred and dispersed under ultrasound, washed and dried to achieve the purpose of pre-dispersion treatment. Then, polyvinyl pyrrolidone is used as a surfactant, N-methyl pyrrolidone is used as a dispersant, and water is used as a solvent to form a concentrated slurry with carbon nanotubes, which is placed in a sand mill for dispersion, wherein the mass ratio of polyvinyl pyrrolidone, N-methyl pyrrolidone, water and carbon nanotubes is 5:5:80:1, and after dispersion, an appropriate amount of water is added to dilute it to a sprayable state. Then, according to the mass ratio of 60%, 26%, 6%, and 4%, the raw materials such as 10μm flake graphite powder, 2123 phenolic resin, pre-dispersed short carbon fiber, long fiber, etc. are weighed and mixed, and an appropriate amount of carbon nanotube slurry is sprayed while mixing, and the mixture is dried after being evenly mixed, so that the mass of carbon nanotubes in the mixture is about 4%. The dried mixture is placed in a V-shaped mixing device for mixing for 5 hours, and then the mixed powder is weighed and filled into a mold for heating and pressing. The pressing pressure is controlled to be 20MPa during hot pressing. After the pressing starts, the temperature is increased to 110℃ at a heating rate of 5℃ / min and kept warm for 0.5h; then the temperature is increased to 180℃ and kept warm for 30min for solidification; after the insulation is completed, cooling is started, and the pressure is reduced step by step during the cooling process, by 3mPa every 20℃, and the pressure is reduced to about 4Mpa when cooled to about 100℃, and finally cooled to room temperature for demolding to obtain a green body. The green body is transferred to the carbonization furnace for carbonization treatment under nitrogen protection, firstly, the temperature is raised to 180℃ for 0.5h and kept for 10min, then the temperature is raised to 260℃ for 3h and kept for 10min, then the temperature is further raised to 400℃ for 4h and kept for 10min, then the temperature is further raised to 600℃ for 30h and kept for 6h, then the temperature is further raised to 850℃ for 6h and kept for 5h, then the temperature is lowered to 600℃ for 4h and kept for 2h, then the temperature is lowered to 400℃ for 2h, and then the product is cooled to room temperature and taken out of the furnace. The product is washed with water to remove the residual impurities on the surface to obtain the C / C composite cathode plate.
[0077] The test results show that the bending strength of the C / C composite cathode plate prepared under the conditions of this embodiment is 75 MPa and the density is 1.6-1.8 g / cm 3 The resistance is about 12.2μΩ·m. Figure 1 It can be seen that the long and short fibers are evenly dispersed and there are fewer defects.
[0078] The C / C composite cathode plate and the TiMn alloy anode plate are used together to prepare electrolytic MnO 2 , where the electrolyte is Mn 2+ The concentration is 0.5 mol / L, H 2 SO 4 MnSO with a concentration of 0.5 mol / L 4 -H2 SO 4 System electrolyte, current density is 80A / m 2 Under this process, the cell voltage during electrolysis is 2.18V, and the prepared electrolytic MnO 2 Medium γ-MnO 2 ( Figure 6 ) crystal form accounts for about 92.1%.
[0079] Example 2
[0080] (1) Preparation of TiMn alloy anode plate
[0081] The method of Example 1 was adopted to prepare a TiMn alloy anode plate.
[0082] (2) Preparation of C / C composite cathode plate
[0083] A C / C composite cathode plate is prepared by the method of Example 1, except that: flake graphite powder with a particle size of 10 μm, 2123 phenolic resin, pre-dispersed chopped carbon fibers, long fibers and other raw materials are weighed in a mass ratio of 57%, 30%, 7% and 3% and mixed, and an appropriate amount of carbon nanotube slurry is sprayed into the mixture while mixing. After mixing evenly, the mixture is dried so that the mass of carbon nanotubes in the mixture is about 3%.
[0084] The test results show that the bending strength of the C / C composite cathode plate prepared under the conditions of this embodiment is 66 MPa and the density is 1.6-1.8 g / cm 3 The resistance is about 14.3μΩ·m.
[0085] The C / C composite cathode plate and the TiMn alloy anode plate are used together to prepare electrolytic MnO 2 , where the electrolyte is Mn 2+ The concentration is 0.5 mol / L, H 2 SO 4 MnSO with a concentration of 0.3 mol / L 4 -H 2 SO 4 System electrolyte, current density is 40A / m 2 Under this process, the cell voltage during electrolysis is 1.81V, and the prepared electrolytic MnO 2 Medium γ-MnO 2 The crystal form accounts for about 89.3%.
[0086] Example 3
[0087] (1) Preparation of TiMn alloy anode plate
[0088] The method of Example 1 was adopted to prepare a TiMn alloy anode plate.
[0089] (2) Preparation of C / C composite cathode plate
[0090] A C / C composite cathode plate is prepared by the method of Example 1, except that: flake graphite powder with a particle size of 10 μm, 2123 phenolic resin, pre-dispersed chopped carbon fibers, long fibers and other raw materials are weighed in a mass ratio of 65%, 23%, 8% and 2% and mixed, and an appropriate amount of carbon nanotube slurry is sprayed into the mixture while mixing. After mixing evenly, the mixture is dried so that the mass of carbon nanotubes in the mixture is about 2%.
[0091] The test results show that the bending strength of the C / C composite cathode plate prepared under the conditions of this embodiment is 70 MPa and the density is 1.6-1.8 g / cm 3 The resistance is about 14.5μΩ·m.
[0092] The C / C composite cathode plate and the TiMn alloy anode plate are used together to prepare electrolytic MnO 2 , where the electrolyte is Mn 2+ The concentration is 0.5 mol / L, H 2 SO 4 MnSO with a concentration of 0.4 mol / L 4 -H 2 SO 4 System electrolyte, current density is 60A / m 2 Under this process, the cell voltage during electrolysis is 2.01V, and the prepared electrolytic MnO 2 Medium γ-MnO 2 The crystal form accounts for about 91.2%.
[0093] Example 4
[0094] (1) Preparation of TiMn alloy anode plate
[0095] The method of Example 1 was adopted to prepare a TiMn alloy anode plate.
[0096] (2) Preparation of C / C composite cathode plate
[0097] A C / C composite cathode plate was prepared by the method of Example 1, except that: flake graphite powder with a particle size of 10 μm, 2123 phenolic resin, pre-dispersed chopped carbon fibers, long fibers and other raw materials were weighed in a mass ratio of 56%, 28%, 8% and 4% and mixed, and an appropriate amount of carbon nanotube slurry was sprayed into the mixture while mixing. The mixture was mixed evenly and then dried so that the mass of carbon nanotubes in the mixture was about 4%.
[0098] The test results show that the bending strength of the C / C composite cathode plate prepared under the conditions of this embodiment is 68 mPa and the density is 1.6-1.8 g / cm 3 The resistance is about 14.3μΩ·m.
[0099] The C / C composite cathode plate and the TiMn alloy anode plate are used together to prepare electrolytic MnO 2 , where the electrolyte is Mn 2+ The concentration is 0.5 mol / L, H 2 SO 4 MnSO with a concentration of 0.6 mol / L 4 -H 2 SO 4 System electrolyte, current density is 90A / m 2 Under this process, the cell voltage during electrolysis is 2.53V, and the prepared electrolytic MnO 2 Medium γ-MnO 2 The crystal form accounts for about 94%.
[0100] Example 5
[0101] (1) Preparation of TiMn alloy anode plate
[0102] The method of Example 1 was adopted to prepare a TiMn alloy anode plate.
[0103] (2) Preparation of C / C composite cathode plate
[0104] A C / C composite cathode plate is prepared by the method of Example 1, except that: flake graphite powder with a particle size of 10 μm, 2123 phenolic resin, pre-dispersed chopped carbon fibers, long fibers and other raw materials are weighed in a mass ratio of 63%, 24%, 8% and 2% and mixed, and an appropriate amount of carbon nanotube slurry is sprayed into the mixture while mixing. After mixing evenly, the mixture is dried so that the mass of carbon nanotubes in the mixture is about 3%.
[0105] The test results show that the bending strength of the C / C composite cathode plate prepared under the conditions of this embodiment is 72 mPa and the density is 1.6-1.8 g / cm 3 The resistance is about 13.7μΩ·m.
[0106] The C / C composite cathode plate and the TiMn alloy anode plate are used together to prepare electrolytic MnO 2 , where the electrolyte is Mn 2+ The concentration is 0.5 mol / L, H 2 SO 4 MnSO with a concentration of 0.8 mol / L 4 -H 2 SO 4 System electrolyte, current density is 110A / m 2 Under this process, the cell voltage during electrolysis is 2.79V, and the prepared electrolytic MnO 2 Medium γ-MnO 2The crystal form accounts for about 93.1%.
[0107] Comparative Example 1
[0108] A TA1Ti plate with a thickness of 1.5 mm was used as an anode and combined with the C / C composite cathode plate prepared in Example 1 to prepare electrolytic MnO 2 , where the electrolyte is Mn 2+ The concentration is 0.5 mol / L, H 2 SO 4 MnSO with a concentration of 0.5 mol / L 4 -H 2 SO 4 System electrolyte, current density is 80A / m 2 .
[0109] After testing, the cell voltage during electrolysis under this process was 2.6V, and the voltage rose slowly. 2 Medium γ-MnO 2 The crystal form accounts for about 87.1%.
[0110] Comparative Example 2
[0111] (1) Preparation of TiMn alloy anode plate
[0112] The method of Example 1 was adopted to prepare a TiMn alloy anode plate.
[0113] (2) Preparation of C / C composite cathode plate
[0114] The C / C composite cathode plate was prepared by the method of Example 1, except that no carbon nanotube slurry was added.
[0115] The results show that the flexural strength of the C / C composite material prepared under the comparative example is 66 MPa and the density is 1.6-1.8 g / cm 3 The resistance is about 19.2μΩ·m.
[0116] The C / C cathode plate prepared under the comparative example conditions and the TiMn-Ti anode were used together to prepare electrolytic MnO 2 , where the electrolyte is Mn 2+ The concentration is 0.5 mol / L, H 2 SO 4 MnSO with a concentration of 0.5 mol / L 4 -H 2 SO 4 System electrolyte, current density is 80A / m 2 Under this process, the cell voltage during electrolysis is 2.35V, and the prepared electrolytic MnO 2 Medium γ-MnO 2The crystal form accounts for about 90.4%. The results show that when no carbon nanotubes are added, the C / C cathode strength decreases slightly, the resistance increases, and then the resistance of the electrolysis system increases and the cell voltage increases. 2 Energy consumption increases, and electrolysis of MnO 2 Medium γ-MnO 2 The crystalline content is reduced.
[0117] Comparative Example 3
[0118] (1) Preparation of TiMn alloy anode plate
[0119] The method of Example 1 was adopted to prepare a TiMn alloy anode plate.
[0120] (2) Preparation of C / C composite cathode plate
[0121] The method of Example 1 is adopted to prepare a C / C composite cathode plate, except that: all the fiber raw materials are added to chopped carbon fibers, excluding long carbon fibers, and flake graphite powder with a particle size of 10 μm, 2123 phenolic resin, and pre-dispersed chopped carbon fibers are weighed and mixed in a mass ratio of 60%, 26%, and 10%.
[0122] The test results show that the bending strength of the C / C composite cathode plate prepared under the conditions of this embodiment is 59 MPa and the density is 1.6-1.8 g / cm 3 About, the resistance is 12.5μΩ·m.
[0123] The C / C composite cathode plate and the TiMn alloy anode plate are used together to prepare electrolytic MnO 2 , where the electrolyte is Mn 2+ The concentration is 0.5 mol / L, H 2 SO 4 MnSO with a concentration of 0.5 mol / L 4 -H 2 SO 4 System electrolyte, current density is 80A / m 2 Under this process, the cell voltage during electrolysis is 2.19V, and the prepared electrolytic MnO 2 Medium γ-MnO 2 The crystal form accounts for about 91.9%. The results show that if the C / C cathode is not reinforced with long and short carbon fibers but with single short fibers, the bending strength of the C / C composite cathode material is significantly reduced, while other properties are less affected.
Claims
1. A combined electrode, characterized in that: Including C / C composite cathode plate and TiMn alloy anode plate; The preparation method of the C / C composite cathode plate comprises: mixing raw materials including graphite powder, phenolic resin and carbon fiber, and then adding carbon nanotube slurry to obtain a mixture; volatilizing the solvent from the mixture, and then adding the mixture into a mold for hot pressing to obtain a green body; placing the green body in a carbonization furnace for carbonization treatment to obtain; The mass ratio of the graphite powder, phenolic resin, carbon fiber and carbon nanotube is 55-65:20-30:8-12:2-4; The carbon fiber includes short chopped carbon fiber and long carbon fiber; The preparation process of the TiMn alloy anode plate is as follows: coating a manganese-containing slurry on the surface of a titanium substrate to obtain a TiMn green body; performing low-temperature degreasing and dehydrogenation on the TiMn green body under vacuum conditions not exceeding 600° C., then filling the TiMn green body with an inert gas and heating it to not more than 800° C. for medium-temperature manganese infiltration, and then continuing to heat it to above 850° C. for high-temperature manganese infiltration to obtain a TiMn-Ti plate; and immersing the TiMn-Ti plate in an acid solution and then washing it to obtain a TiMn alloy anode plate.
2. A combined electrode according to claim 1, characterized in that: The length of the short carbon fiber is 3-5 mm; the length of the long carbon fiber is 8-12 mm; The mass ratio of the chopped carbon fiber to the long carbon fiber is 6-8:2-4; The carbon fiber is surface pretreated by a solution that can reduce the hydrophobicity on the surface of the carbon fiber and the friction between the fibers.
3. A combined electrode according to claim 1, characterized in that: The graphite powder is flake graphite powder with a particle size of 6 to 20 μm; The phenolic resin is a thermosetting phenolic resin; The carbon nanotube slurry comprises carbon nanotubes, polyvinyl pyrrolidone, N-methyl pyrrolidone and water; The mass concentration of the carbon nanotubes in the carbon nanotube slurry is 0.3-8%.
4. A combined electrode according to claim 1, characterized in that: The hot pressing molding process is as follows: controlling the pressing pressure to be 10-40 MPa, first heating the temperature to 100-120°C at a heating rate of 1-5°C / min and keeping the temperature for 0.5-1h, then continuing to heat the temperature to 160-190°C and keeping the temperature for 20-40min, then cooling and reducing the pressure to a temperature of 90-110°C and a pressure of 3-8MPa, and then continuing to cool to room temperature; the pressure reduction rate is a pressure reduction of 2-4MPa for every 10-20°C temperature reduction.
5. A combined electrode according to claim 1 or 4, characterized in that: The carbonization treatment process is as follows: in a protective atmosphere, heating to 160-190°C for 0.5-1h and keeping warm for 10-30min, heating to 240-300°C for 2-3h and keeping warm for 10-30min, heating to 390-450°C for 4-6h and keeping warm for 10-30min, heating to 580-620°C for 25-30h and keeping warm for 4-6h, heating to 840-860°C for 6-8h and keeping warm for 5-8h, then cooling to 580-620°C for 4-6h and keeping warm for 1-2h, cooling to 390-430°C for 1-2h and naturally cooling to room temperature.
6. The application of a combined electrode according to claim 1, characterized in that: Used in the preparation of electrolytic MnO2.
Citation Information
Patent Citations
Method for preparing high-deformation resistance titanium anode from electrolytic manganese dioxide
CN105887133A
Preparation method of Ti-Mn-diffusion titanium anode plate for electrolytic manganese dioxide
CN101694001A
Carbon-carbon composite material as well as preparation method and application thereof in production of electrolytic manganese dioxide
CN109020596A
Carbon nanotube modified reinforced graphite electrode and preparation method thereof
CN110204349A